Analytical Study on Propagation Dynamics of Optical Beam in Parity-Time Symmetric Optical Couplers*Supported by the National Natural Science Foundation of China under Grant No. 11465008, the Hunan Provincial Natural Science Foundation under Grant Nos. 2015JJ4020 and 2015JJ2114, the Scientific Research Fund of Hunan Provincial Education Department under Grant No. 14A118. (1st April 2015) - Zhou, Zheng; Zhu, Bo; Zhang, Li-Juan
Abstract We present exact analytical solutions to parity-time (PT) symmetric optical system describing light transport in PT-symmetric optical couplers. We show that light intensity oscillates periodically between two waveguides for unbroken PT-symmetric phase, whereas light always leaves the system from the waveguide experiencing gain when light is initially input at either waveguide experiencing gain or waveguide experiencing loss for broken PT-symmetric phase. These analytical results agree with the recent experimental observation reported by Rüter et al. [Nat. Phys. 6 (2010) 192]. Besides, we present a scheme for manipulating PT symmetry by applying a periodic modulation. Our results provide an efficient way to control light propagation in periodically modulated PT-symmetric system by tuning the modulation amplitude and frequency.